2019
DOI: 10.31202/ecjse.474363
|View full text |Cite
|
Sign up to set email alerts
|

Past to Present: Solar Chimney Power Technologies

Abstract: This study introduces the solar chimney power technology, which is a solar thermal energy system. One of the renewable energy resources, this system is an energy transformation system in which solar energy and wind energy are used together. In this system, the air that is heated with solar energy ensures the production of electric energy by moving upwards with the suction effect of the chimney and rotating the turbine that is placed inside the chimney. In this review, the main principles and characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
3
0
1
Order By: Relevance
“…According to the countries' energy policies, solar energy is expected to meet 11% of global electrical energy consumption in 2050 [9]. In short-term plans, it is estimated that renewable energy sources will be the energy source with the fastest growth rate with a growth rate of 7.6% until 2030 [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the countries' energy policies, solar energy is expected to meet 11% of global electrical energy consumption in 2050 [9]. In short-term plans, it is estimated that renewable energy sources will be the energy source with the fastest growth rate with a growth rate of 7.6% until 2030 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy can be taken as the most efficient energy source because it is a clean renewable energy source and is possible to widely distributed [3]. There are many different ways of using solar radiation in the forms of power for heat engines, thermoelectric power generators (such as by Peltier elements or steam engines), photovoltaic cells for direct electricity production, crop dying, power for refrigerators and air conditioners, desalination of sea water and domestic hot water production [4][5][6][7][8][9]. Concentrating solar power (CSP) gets public attention in a wide extent and is thought as one of the most efficient alternatives [10].…”
Section: Introductionmentioning
confidence: 99%
“…They optically investigated an open receiver of a conical cavity in the shape of a helical tube in order to improve the receiver's optical performance. It is revealed that the helical conical shape with an aperture area of 0.01606 m² absorbed an average flux value of about 2.6 x 105 W/ m² [8]. Another investigation has been run by Rafeu and Kadir (2012) used three experimental models with various geometrical sizes and solar dish concentrators with a diameter of about 0.5 m in order to search the geometry's effect on a solar temperature and irradiation by maximizing the solar fraction under the Malaysian environment.…”
Section: Introductionmentioning
confidence: 99%
“…Şanlıurfa'daki rüzgâr yakalayıcılarının sadece eyvanı havalandırmak için tasarlanmaları da özgün niteliklerinden biridir. Bazı evlerin eyvanlarını havalandıran bir ya da iki rüzgâr yakalayıcının varlığı ise yine Irak'taki örneklerle benzerlik oluşturmaktadır.Günümüzde kullanılan bina bileşenlerinin çevre üzerinde oluşturacağı etkiler gittikçe daha çok önem kazanmaktadır[56]. Kökleri Antik dönemlere dayanan geleneksel rüzgâr yakalayıcılarının günümüze kalan örnekleri birçok ülkede özellikle korunmakta, sürdürülebilir pasif havalandırma ve soğutma sistemleri için ilham kaynağı olmaktadır.…”
unclassified